Iron oxide@chlorophyll clustered nanoparticles eliminate bladder cancer by photodynamic immunotherapy-initiated ferroptosis and immunostimulation - Chin, Yu-Cheng; Yang, Li-Xing; Hsu, Fei-Ting; Hsu, Che-Wei; Chang, Te-Wei; Chen, Hsi-Ying; Chen, Linda Yen-Chien; Chia, Zi Chun; Hung, Chun-Hua; Su, Wu-Chou; Chiu, Yi-Chun; Huang, Chih-Chia; et al. (Journal of nanobiotechnology, 2022)
The escape of bladder cancer from immunosurveillance causes monotherapy to exhibit poor efficacy; therefore, designing a multifunctional nanoparticle that boosts programmed cell death and immunoactivation has potential as a treatment strategy. Herein, we developed a facile one-pot coprecipitation reaction to fabricate cluster-structured nanoparticles (CNPs) assembled from Fe 3 O 4 and iron chlorophyll (Chl/Fe) photosensitizers. This nanoassembled CNP, as a multifunctional theranostic agent, could perform red-NIR fluorescence and change the redox balance by the photoinduction of reactive oxygen species (ROS) and attenuate iron-mediated lipid peroxidation by the induction of a Fenton-like reaction. The intravesical instillation of Fe 3 O 4 @Chl/Fe CNPs modified with 4-carboxyphenylboronic acid (CPBA) may target the BC wall through glycoproteins in the BC cavity, allowing local killing of cancer cells by photodynamic therapy (PDT)-induced singlet oxygen and causing chemodynamic therapy (CDT)-mediated ferroptosis. An interesting possibility is reprogramming of the tumor microenvironment from immunosuppressive to immunostimulatory after PDT-CDT treatment, which was demonstrated by the reduction of PD-L1 (lower “off” signal to the effector immune cells), IDO-1, TGF-β, and M2-like macrophages and the induction of CD8 + T cells on BC sections. Moreover, the intravesical instillation of Fe 3 O 4 @Chl/Fe CNPs may enhance the large-area distribution on the BC wall, improving antitumor efficacy and increasing survival rates from 0 to 91.7%. Our theranostic CNPs not only demonstrated combined PDT-CDT-induced cytotoxicity, ROS production, and ferroptosis to facilitate treatment efficacy but also opened up new horizons for eliminating the immunosuppressive effect by simultaneous PDT-CDT.